Faktor-Faktor yang Mempengaruhi Pengungkapan Corporate Social Responsibility di dalam Laporan Sustainability (Studi Empiris Pada Perusahaan yang listing di Bursa Efek Indonesia Tahun 2010-2013) - Rohmah, Dita (Esensi: Jurnal Bisnis dan Manajemen, 2015)
The study aims to examine the effect of corporate governance, firm size, and profitability to corporate social responsibility disclosure in sustainability report. The mechanism of corporate governance used are independent commissioner, institutional ownership, and foreign ownership.This research is a quantitative study using scientific research in the form of positive economics. The nature and type of this research is descriptive with the method used by literature survey. Data used is secondary data obtained from www.idx.co.id and corporate websites. The analytical method used is multiple linear regression analysis with SPSS version 22. The populations in this study are all companies listed on the Indonesia Stock Exchange during the period 2010 until 2013. Samples are taken by purposive sampling method amount 21companies with 4 years observation. Based on the results of multiple regression analysis with a significant level of 5%, the results of this study concluded that: (1) Independent Commissary does not signicantly influence the effect on the disclosure of CSR in the sustainability report with the significant value 0.390 > 0.05. (2) Institutional Ownership has a significant effect on the disclosure of CSR in the sustainability report with the significant value 0.003 < 0.05. (3) Foreign Ownership does not signicantly influence the effect on the disclosure of CSR in the sustainability report with the significant value 0.221 > 0.05. (4) Firm Size has a significant effect on the disclosure of CSR in the sustainability report with the significant value 0.000 < 0.05. (5) Profitability has a significant effect on the disclosure of CSR in the sustainability report with the significant value 0.001< 0.05.DOI: 10.15408/ess.v5i2.2347